SIGHT—A System for Solvent‐Tight Incubation and Growth Monitoring in High Throughput - Jakob Rönitz; Felix Herrmann; Benedikt Wynands; Tino Polen; Nick Wierckx (Engineering in Life Sciences)
ABSTRACT Physiological characterization of microorganisms in the context of solvent tolerance is a tedious process with a high investment of manual labor while often being limited in throughput capability simultaneously. Therefore, we developed a small‐scale solvent‐impervious cultivation system consisting of screw cap‐sealed glass vials in combination with a 3D‐printed vial holder for the Growth Profiler (EnzyScreen) platform. Components and cultivation conditions were empirically tested, and a suitable setup was found for the intended application. To demonstrate the capability of this cultivation system, an adaptive laboratory evolution was performed to further increase the tolerance of Pseudomonas taiwanensis GRC3 toward styrene. This approach yielded heterogenic cultures with improved growth performances in the presence of styrene from which individual clones were isolated and characterized in high throughput. Several clones with improved growth in the presence of 1% (v/v) styrene were analyzed through whole‐genome sequencing, revealing mutations in the co‐chaperone‐encoding gene dnaJ, RNA polymerase α subunit‐encoding gene rpoA, and loss‐of‐function mutations in the ttgGHI solvent efflux pump repressor encoded by ttgV. The developed cultivation system has proven to be a very useful extension of the Growth Profiler, as it reduces manual workload and allows high‐throughput characterization.